Fertility preservation in transgender men and the need for uniform, comprehensive counseling - Selena U. Park, M.D; Devika Sachdev, M.D; Shelley Dolitsky, M.D; Matthew Bridgeman, M.L.I.S; Mark V. Sauer, M.D., M.S; Gloria Bachmann, M.D., M.S.S; Juana Hutchinson-Colas, M.D., M.B.A (Elsevier, 2022)
Objective: To review the literature to assess best practices for counseling transgender men who desire gender-affirming surgery on fertility preservation options. Design: A scoping review of articles published through July 2021. Setting: None. Patient(s): Articles published in Cochrane, Web of Science, PubMed, Science Direct, SCOPUS, and Psychinfo. Intervention(s): None. Main Outcome Measure(s): Papers discussing transgender men, fertility preservation (FP), and FP counseling. Result(s): The primary search yielded 1,067 publications. After assessing eligibility and evaluating with a quality assessment tool, 25 articles remained, including 8 reviews, 5 surveys, 4 consensus studies, 3 retrospective studies, 3 committee opinions, and 2 guidelines. Publications highlighted the importance of including the following topics during counseling: (1) FP and family building options; (2) FP outcomes; (3) effects of testosterone therapy on fertility; (4) contraception counseling; (5) attitudes toward family building; (6) consequences of transgender parenting; and (7) barriers to success. Conclusion(s): Currently, there is a lack of standardization for comprehensive counseling about FP for transgender men. Standardized approaches can facilitate conversation between physicians and transgender men and ensure patients are making informed decisions regarding pelvic surgery and future family building plans.